Cultural System in Ancient India: Exploring Health and Healing in Ancient Indian Societies through Language and Literature (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The present research uses immoderately the original Sanskrit, Pali and Tamil sourcebooks. The boggy stereotypes current in the theme abstain from this reappraisal to provide more expansive and more focused perspectives on health and healing in ancient Indian societies. This orientation towards the history of medicine appears critically justified since the available literature on medical history in India largely continues in a desideratum.